2014
DOI: 10.3109/13880209.2013.868493
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivity screening of fiveCentaureaspecies andin vivoanti-inflammatory activity ofC. athoa

Abstract: C. athoa is suggested to be a potential source of lead compounds for inflammatory diseases due to the significant in vitro and in vivo anti-inflammatory results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 21 publications
1
20
0
1
Order By: Relevance
“…Similar to our result, Talhouk et al 44 reported that water extract of C. ainetensis inhibited IL-6 production in a dose-dependent manner. In addition, in vivo anti-inflammatory effects of some Centaurea species were reported as well by Erel et al 45 and Koca et al 46 The present study indicates that induction or inhibition of inflammatory cytokines by ethanolic extract of C. solstitialis is cell-type dependent.…”
Section: Discussionsupporting
confidence: 82%
“…Similar to our result, Talhouk et al 44 reported that water extract of C. ainetensis inhibited IL-6 production in a dose-dependent manner. In addition, in vivo anti-inflammatory effects of some Centaurea species were reported as well by Erel et al 45 and Koca et al 46 The present study indicates that induction or inhibition of inflammatory cytokines by ethanolic extract of C. solstitialis is cell-type dependent.…”
Section: Discussionsupporting
confidence: 82%
“…Many Centaurea species are used traditionally for medicinal purposes, including Centaurea pulchella, Centaurea drabifolia, Centaurea triumfettii, Centaurea depressa, and Centaurea virgate. Various biological activities of the members of the genus Centaurea L. have been reported previously, such as cytogenetic (Radic et al, 2005), antiinflammatory (Garbacki et al, 1999;Erel et al, 2011Erel et al, , 2014, anticancer , and cytotoxic activities (Seghiri et al, 2009;Ahmed and Kamel, 2014). The chemical composition of the members of this genus was also reported in other studies (Dural et al, 2003;Beltagy, 2015).…”
Section: Introductionmentioning
confidence: 69%
“…In comparison with a previous study used the ultrasound assisted extraction and conducted in Turkey, the extraction yield of C. iberica using different solvents (chloroform, methanol, n-Hexane) was (1.46%, 7.04%, 1.14%), respectively. The difference in yield can be explained by different environmental factors (Erel et al, 2014). In this study, the ultrasound assisted extraction technique was used.…”
Section: Discussionmentioning
confidence: 99%